Local host ant usage of scarce large blue Phengaris teleius and dusky large blue P. nausithous (Lepidoptera: Lycaenidae) at Goričko Nature Park (NE Slovenia) - Valerija Zakšek; Barbara Zakšek; Gregor Bračko; Marijan Govedič; Rudi Verovnik (Natura Sloveniae)
In our contribution we report on the local host ants of two threatened and protected butterfly species, the scarce large blue (Phengaris teleius) and the dusky large blue (P. nausithous) at Goričko (NE Slovenia), which hosts one of the largest and the most important metapopulation for both species of large blues in Slovenia. Larvae of both species are developing in Myrmica ant nests and different ant species may be used as larval hosts in different parts of the species range. During our study, seven species of potential host ants of the genus Myrmica were found at 12 selected sampling sites. A total of 142 ant nests were examined for the presence of Phengaris larvae. Larvae of P. teleius were found in 25 nests of three ant species: M. scabrinodis, M. rubra and M. gallienii, while larvae of P. nausithous were found in 9 nests, all of M. rubra. The results of the present study provide the first insight into the local host ants of the two Phengaris species in Slovenia and could serve as an important source for active conservation of both species in Slovenia.